Companion moto : IoT - based motorcycling jacket for enhanced safety. - Aparici, Christian Lordenz A. Fariscal, Dainty S. Morales, Josias Seymour R. Sempio, Jenard Christopher m. Soliven, Reynel n. 4 0 16; 5
ABSTRACT: STATEMENT OF THE PROBLEM: This study aims to assess the impact of Companion Moto in terms of enhancing the safety of motorcycle users within Metro Manila. RESEARCH METHODOLOGY: The research used a quasi-experimental design, in which the locale was focused on motorcycle riders within Metro Manila. The visibility measurement used one group pre-test-only design using a Motorcycle Visibility Questionnaire, while the post-test-only design was used for Web Application Evaluation Questionnaire and System Usability Scoring. The results of the questionnaires were analyzed using Likert Scale Analysis and Paired T-test evaluation. And finally, prototype testing was utilized to evaluate the crash-sensing system and other key features of the system. SUMMARY OF FINDINGS: The four objectives are as follows with their accompanying results: a) to design a wireless connection between the jacket and motorcycle, resulting with a t-value of 8.144, b) to design a crash-sensing system with the following prototype testing, GSM Testing with mean score (time) of 8.074%; GPS Testing with longtitude and latitude weighted mean 0.00075% and 0.000023%; Gyroscope Testing with a right and left angle mean of 4% and 6%, c) to design a Web Application that can store user's with subcomponents compatibility, usability, and functionality which are deemed as very satisfied by users, d) to evaluate system's overall functionality from user's perspective having a 52.83% promoter, 22.64% passive, and 24.53% detractor. CONCLUSION: With T-test evaluation, objective I concluded that Companion Moto has a significant effect on motorcycle visibility with a robust battery life. As for objective II, the data gathered from prototype testing suggested that the cash-system was developed successfully. For objective III, the Web Application created is compatible with both desktop and mobile device and was able to store the inputted data by the users. Lastly, for objective IV, the System Usability Score (SUS) revealed that most respondents expressed a high level of satisfaction, through some remain in the passive and dissatisfaction sections. RECOMMENDATION: Various aspects can be considered for improving the system, such as battery life, jacket design, GPS tracking system, plug-and-play prototype, use of cloud technology, utilization of the gyroscope for turning signal lights, and use of the motorcycle's ECU for additional features (monitoring of speed limit, exhaust emission, etc.).
Undergraduate Thesis: (Bachelor of Science in Computer Enginenering) - Pamantasan ng Lungsod ng Maynila , 2024.
Keywords: 2 -- 0; 6; 20; 20; 2